FORESIGHT - FORECASTING PROSPECTS OF TECHNOLOGICAL RE-ENGINEERING OF THE ENTERPRISE - POPOV, ALEXANDER (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The work is devoted to the study of the essence, distinctive principles and methods of foresight as a method of forecasting the prospects of technological reengineering of domestic enterprises, which involves increasing the effectiveness of state regulation of the main parameters of socio-economic development and is based on a set of developed economic forecasts of reengineering transformations. It is substantiated that the foresight is the optimal tool for qualitative planning of the country's economy at the current stage, as a relatively new management technology that is used at the macro and micro level to actively design the future state of small, medium and large socio-economic systems. It has been established that foresight can be considered as a tool for managing strategic competitiveness at the micro level, which is based on the prediction of future changes and the formation of such qualitative characteristics of the functioning of the entrepreneurial structure that allow it to be capable of producing innovations. It has been determined that the difference between future development research and foresight is that not all methods of future analysis are included in the foresight toolkit. The study focuses on a strategic approach to the introduction of innovative technologies in the conditions of a country that does not have a full-fledged national innovation system. It has been proven that such an option is the purchase of licenses for technologies necessary for carrying out reengineering and innovative transformations of production. Features of license evaluation practice are described. The display of the process of preliminary forecasting of the results of the technological rehabilitation of the enterprise on the basis of reengineering with the application of the purchased license is presented in a model form.
Keywords: foresight; forecasting; model; license; technological reengineering; uncertainty